Vienna (from the Bastions) - Wallis, Robert, 1794-1878 (engraver):::Creator::::::::::::; Bartlett, William Henry, 1809-1854 (artist):::Contributor::::::::::::; Beattie, William, 1793-1875 (author):::Contributor:::::::::::: (George Virtue; London; United Kingdom)
Engravings with a view of Vienna from the bastions